Analisis Tingkat Keamanan File Dokumen Menggunakan Algoritma Advanced Encryption Standard (AES) - -, Hasan Shadzily; Bambang Sujatmiko (Inovate, 2025)
Data security in document files that are sent or stored digitally is one of the problems in the current technological era. Especially the use of digital platforms to share information can be a target for data theft, so a solution is needed to protect the confidentiality and integrity of data sent over the internet network. One way to solve this problem is to implement a secure and easy-to-implement cryptographic algorithm, one of which is the Advanced Encryption Standard (AES) with a key length of 128 bits. AES is an algorithm that has proven its security and is widely used to protect data in various applications. By encrypting document files using AES, data sent via digital platforms can be protected and prevent access from unauthorized parties, because only those who have the key can decrypt it. The results of the ciphertext randomness test using Shannon entropy obtained an average entropy value of 7.96. This value proves that the randomness level of the ciphertext is very high, approaching the maximum value of 8 which produces a random ciphertext, thus strengthening data security from potential pattern analysis or cryptanalyst attacks.